COST-BENEFIT ANALYSIS IN THE NEW LEGISLATION ON ENERGY EFFICIENCY - Mihaela, IONESCU-SAS (Strategii Manageriale, 2015)
In this paper the author presents some aspects of a more comprehensive analysis on the macroeconomic effects it generates new regulations on energy efficiency in the European Union. Are presented for this purpose EU targets 20% of primary energy consumption by 2020 and those relating to improving energy efficiency in the perspective of 2030. The analysis consists in determining and assessing costs, benefits and energy efficiency is completed by develop conclusions and recommendations in order to help build a power system efficient, safe, competitive, reducing dependence on energy imports and create new opportunities for growth.